VARIAÇÃO LONGITUDINAL DA DENSIDADE BÁSICA DA MADEIRA DE CLONES DE EUCALIPTO - CACAU, Filipe Valadão do Prado; DUARTE, Milena da Silva; URBANO, Edilson; FALCÃO, Karina dos Santos; SILVA, Raíssa Falcão da Silva (ANAIS DO ENIC, 2025)
-